Asymmetric double-image encryption using twin decomposition in fractional Hartley domain - Kumar, Jaideep; Singh, Phool; Yadav, Ak (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
Twin decomposition, consisting of equal and random modulus decompositions, not only makes a cryptosystem asymmetric but also resists special attack. A new double-image asymmetric cryptosystem using twin decomposition in fractional Hartley domain is proposed. An input grayscale image, bonded with another grayscale image as its phase mask, is transformed via fractional Hartley transform. Equal modulus decomposition is applied on the resulting image, giving us two intermediate images. One of them is subjected to another fractional Hartley transform followed by random modulus decomposition, whereas the other serves as the first private key. The application of random modulus decomposition also results in two images: encrypted image and the second private key. During the process of decryption, firstly the encrypted image is combined with second private key and thereafter it is subjected to inverse fractional Hartley transform. The resulting image is then combined with the first private key, and followed by another inverse fractional Hartley transform, thus recovering the two original images. The proposed cryptosystem is validated for pairs of grayscale images.
Optica Applicata, Vol. 52, 2022, nr 1, s. 21-35
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; double image encryption; twin decomposition; asymmetric cryptosystem; fractional Hartley transform